180 Comparative Pharmacokinetics of Flunixin Meglumine and Meloxicam in Tilapia (Oreochromis Spp.) - Martin, Miriam S (J Anim Sci, 2021)
Aquaculture is one of the largest growing sectors of the world food supply. There is evidence of pain perception in fish, but analgesic use in aquaculture is limited, as little information is available on the properties of analgesic drugs in fish. The objective was to investigate the comparative pharmacokinetics of flunixin administered intramuscularly and meloxicam administered intramuscularly or orally in tilapia. Two hundred-seventy fish were enrolled and assigned to 1 of 3 treatment groups 1) flunixin meglumine administered intramuscularly at a dose of 2.2 mg/kg; 2) meloxicam administered intramuscularly at a dose of 1 mg/kg; or 3) meloxicam administered orally at a dose of 1 mg/kg. Blood samples were collected from 6 fish per treatment group at 14 timepoints out to 10 days post-drug administration. Plasma drug concentrations were determined using ultra-high pressure liquid chromatography coupled with mass spectroscopy. The mean and standard error of the plasma concentration were calculated for each treatment at each timepoint. The plasma concentration versus time data were analyzed with a non-compartmental approach using a commercially available software (Phoenix®, Version 8.3, Certara, Inc., Princeton, NJ, USA). Flunixin reached a mean maximum concentration (C(max)) of 4826.7 ng/mL at 0.5 h, had a terminal half-life (T(1)/(2)) of 0.5h, and an area under the concentration time curve extrapolated to infinity (AUC(INF_obs)) of 25,261.62 h*ng/mL. Intramuscular meloxicam had a T(1)/(2) of 9.4 h after reaching a C(max) of 11.3 ng/mL at 2 h, with an AUC(INF_obs) of 150.31 h*ng/mL. Oral meloxicam has a T(1)/(2) of 1.9 h after reaching a C(max) of 72.2 ng/mL at 2 h, with an AUC(INF_obs) of 400.83 h*ng/mL. In conclusion, flunixin, when administered intramuscularly, reaches sufficient plasma concentrations to potentially have an effect, while meloxicam when administered intramuscularly or orally at the given dosage likely does not due to the relatively low plasma concentration.